REVISITING THE WORKING MEMORY–READING COMPREHENSION LINK: EVIDENCE FROM INDONESIAN EFL UNIVERSITY STUDENTS - Silvi Ramadhani; Dodi Settiawan (Journal of English and Arabic Language Teaching, 2026)
Working memory is widely regarded as a key cognitive resource underlying reading comprehension. Nevertheless, its contribution to academic reading performance in English as a Foreign Language (EFL) context remains inconclusive, particularly when different measures of working memory are employed. This study examined the relationship between working memory and academic reading comprehension among Indonesian EFL university students. Using a quantitative correlational design, data were collected from 33 English Education students through a Backward Digit Span Task and an academic reading comprehension test. Spearman’s rank-order correlation revealed a positive but non-significant association between working memory and academic reading comprehension (ρ = .176, p = .326). Although the direction of the relationship was consistent with theoretical accounts that position working memory as a facilitator of text processing, the effect size was negligible. The findings suggest that working memory, as assessed through a domain-general digit span measure, contributes only marginally to variation in academic reading comprehension. Rather, successful comprehension of academic texts appears to depend on a broader constellation of linguistic and cognitive factors. By providing evidence from an underrepresented EFL higher education context, this study contributes to ongoing discussions concerning the role and measurement of working memory in second-language reading research. Future studies should adopt multidimensional models that incorporate both cognitive and linguistic predictors to achieve a more comprehensive understanding of academic reading performance.